What is my role in teaching English language and teaching to the test if my learners are preparing for standarized exams? - Yunusova Dildora Hamroqulovna (International Scientific and Current Research Conferences, 2023)
The article discusses effective methods for preparing students for standardized language tests, with a focus on improving general English skills and vocabulary. The author emphasizes the importance of using materials that are relevant to the students' proficiency level and engaging them through real-world examples. Motivating students is seen as crucial for their success, as it provides mental and emotional energy. Teachers need to have knowledge of the test structure and assessment standards in order to effectively teach learners and develop appropriate lessons and practice exercises. Assessments and feedback are also important, with opportunities for frequent practice and self-assessment encouraged.